2012
DOI: 10.1177/0885412212451029
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Use by Default

Abstract: Zoning is such a cornerstone of the US planning system that for US planners it may be hard to imagine that one can regulate development without it. But is zoning a widely shared institution? Is it as integral to the planning systems of other ''developed'' nations as it is in the United States? Based on a review of literature and planning documents, this article contrasts land-use regulation in five European countries (England, France, Germany, Sweden, and Russia) to that in the United States. It argues that fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(12 citation statements)
references
References 38 publications
0
9
0
3
Order By: Relevance
“…Law scholars have shown that their preferential use varies according to the country [6]. Depending on local property rights and land-use regulations, the same tool (e.g., zoning) may be used for different planning practices in the United States and Europe [7].…”
Section: Introductionmentioning
confidence: 99%
“…Law scholars have shown that their preferential use varies according to the country [6]. Depending on local property rights and land-use regulations, the same tool (e.g., zoning) may be used for different planning practices in the United States and Europe [7].…”
Section: Introductionmentioning
confidence: 99%
“…German local governments have the power to regulate the use of land within its borders. The German land-use regulation system rests on the principle of functional zoning and-in its basic mechanism-resembles other systems such as land zoning in the United States (e.g., Hirt 2012). The municipalities develop plans of land usage in which they legally dedicate land to specific purposes (Hirt 2012).…”
Section: Institutional Backgroundmentioning
confidence: 99%
“…The German land-use regulation system rests on the principle of functional zoning and-in its basic mechanism-resembles other systems such as land zoning in the United States (e.g., Hirt 2012). The municipalities develop plans of land usage in which they legally dedicate land to specific purposes (Hirt 2012). Changes in the plans for land usage must pass the municipal council and need approval by an upper-tier administration.…”
Section: Institutional Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation for this refers to the much larger amount of public involvement in the planning process of suburban centres in countries such as France and the Netherlands (Bontje/Burdack 2005). Furthermore, less rigid zoning practices in Europe, compared to the US experience, have often been stressed as relevant contextual factors responsible for a transatlantic divergence in spatial urban structure and urban form (see Hirt 2012). While residents and their residential preferences have long been identified as strong drivers of the process of suburbanisation, other influences have been discussed to a much lesser extent, such as the supply side of the housing market or job opportunities for the residents.…”
Section: Observations From 'New' Suburbanisation Studiesmentioning
confidence: 99%